Instructional Approaches for Fostering Self-Regulated Learning in Chemistry Education: A Systematic Literature Review - Munawwarah Munawwarah; Hastuti Agussalim (Universitas Lampung, 2026)
This study aims to identify and analyze instructional approaches used to foster self-regulated learning (SRL) in chemistry education through a systematic literature review (SLR). The review followed the PRISMA guidelines by initially collecting 100 articles from multiple academic databases, including Scopus, Web of Science, ERIC, and Google Scholar. After removing duplicates, 98 records remained and were screened based on titles and abstracts, resulting in 60 relevant studies. These articles were further assessed through full-text evaluation using predefined inclusion and exclusion criteria, leading to the final inclusion of 40 studies for analysis. The data were analyzed using a thematic synthesis approach to categorize instructional strategies and the SRL components they address. The findings reveal that instructional approaches in chemistry education can be classified into six main categories: metacognitive-based instruction, problem-based learning, technology-enhanced learning, assessment-based approaches, flipped classroom models, and cognitive tools. Among these, metacognitive-based instruction emerged as the most dominant approach, primarily supporting the monitoring and evaluation phases of SRL. However, the analysis indicates that the planning phase of SRL remains underrepresented across the reviewed studies. These results highlight an imbalance in the implementation of SRL in chemistry education, where reflective processes are emphasized more than proactive learning planning. Therefore, more integrated instructional designs are needed to explicitly support all phases of SRL, including planning, monitoring, and evaluation. This study contributes to the field by providing a thematic synthesis of instructional approaches and identifying key research gaps for future research.